Managing wolf conflict perspectives in central Portugal - Martins, Raquel Sofia Costa (2021)
Portuguese wolf populations suffered a decrease during the 20th century mainly due to the expansion of road network, increasing number of forest fires, decrease of wild prey populations, and human persecution. This is particularly worrying in Central Portugal, South of River Douro, where populations are small, highly fragmented and isolated, with little genetic variability and instable reproduction, and low density of wild prey. Conflict in this area is aggravated by high levels of livestock depredation, where livestock makes up for more than 90% of wolves diet. This antagonizes Humans towards wildlife, that typically respond by recurring to activities such as illegal pouching or poisoning in order to solve their problem. This problematic is recognized as the first cause of large carnivores’ persecution and population decline. By surveying individual attitudes toward wolves in central Portugal, we believe that it is possible to understand and even predict behaviour towards the specie. This was done using a questionnaire to sample local population, a total of 222 questionnaires from three interest groups (general public, N=119; livestock owners, N=88; and hunters, N=24) were analysed. We measured Attitude, Fear and Knowledge Index, tested correlation between Index and examined which variables influenced Attitudes and Fear. Attitudes towards wolves were positive, even though Fear high and Knowledge was low. We also found that attitudes tend to be more positive with the decrease of fear and the increase of knowledge, and fear tends to decrease with the increase of knowledge. The main variable influencing attitudes negatively was found to be Fear, and age for the livestock owners, where people older than 60 years old tend to have more negative attitude. As for Fear the main influenceable variables belong to the female gender, a low knowledge index and the knowledge/having suffered from wolf depredation. These results can be used to increase locals’ tolerance, by creating tailored conservational measures together with all the stakeholders’ group